Assessing adherence to multiple medications and in daily life among patients with multimorbidity. Issue 10 (3rd October 2017) - Inauen, Jennifer; Bierbauer, Walter; Lüscher, Janina; König, Claudia; Tobias, Robert; Ihle, Andreas; Zimmerli, Lukas; Holzer, Barbara M.; Battegay, Edouard; Siebenhüner, Klarissa; Kliegel, Matthias; Scholz, Urte
Abstract : Objective: Chronic conditions often require multiple medication intake. However, past research has focused on assessing overall adherence or adherence to a single index medication only. This study explored adherence measures for multiple medication intake, and in daily life, among patients with multiple chronic conditions (i.e. multimorbidity). Design: Eighty-four patients with multimorbidity and multiple-medication regimens completed three monthly panel questionnaires. A randomly assigned subsample additionally completed a 30-day daily diary. Main outcome measure : The Non-Adherence Report; a brief self-report measure of adherence to each prescribed medication (NAR-M), and in daily life. We further assessed the Medication Adherence Report Scale (MARS), and a subsample of participants were randomised to electronic adherence monitoring. Results: The NAR-M indicated M = 94.7% adherence at Time 1 ( SD = 9.3%). The NAR-M was significantly correlated with the MARS ( r t 1 = .52, r t 2 = .57, and r t 3 = .65; p < .001), and in tendency with electronically assessed adherence ( r t 2 = .45, r t 3 = .46, p < .10). Variance components analysis indicated that between-person differences accounted for 10.2% of the variance in NAR-M adherence rates, whereas 22.9% were attributable to medication by person interactions. Conclusion: This study highlights the importance and feasibility of studying adherence to multiple medications differentially, and in daily life. Future studies may use these measures to investigate within-person and between-medication differences in adherence.